PENGARUH INFLUENCER MEDIA SOSIAL TERHADAP MINAT PEMBELIAN ULANG PERAN MEDIASI KEPUTUSAN PEMBELIAN - Satria Bayuaji Saputra; Muhammad Sholahuddin (JURNAL LENTERA BISNIS, 2025)
This study aims to explain how influencer credibility, attractiveness, and similarity affect repurchase intention through the mediating role of buying decisions. This study uses a quantitative approach with a survey method, and obtained a total sample size of 195. The sampling technique used non probability sampling with purposive sampling technique. Data analysis using SmartPLS 4.0 software, specifically using Structural Equation Model (SEM) analysis. The findings of this study indicate that Social Media Influencers have an effect on purchasing decisions, the relationship between Social Media Influencers has a positive and insignificant effect on repurchase interest, but the mediating role of purchasing decisions provides a positive and significant influence relationship between social media influencers on repurchase interest.